2000
DOI: 10.1021/bi0009136
|View full text |Cite
|
Sign up to set email alerts
|

Studies of RNA Cleavage by Photolysis of N-Hydroxypyridine-2(1H)-thione. A New Photochemical Footprinting Method

Abstract: N-Hydroxypyridine-2(1H)-thione (N-HPT) has been studied as a photochemical source of hydroxyl radicals for use in photoinitiated nucleic acid footprinting experiments. Steady-state photolysis of dilute aqueous solutions of N-HPT at 350 nm in the presence of a 385 nucleotide 32 P-labeled RNA, the Tetrahymena L-21 ribozyme, resulted in cleavage of the RNA at nucleotide resolution. No cleavage of the RNA occurred in the absence of light or in the absence of N-HPT. Photolysis of the analogous pyridine lacking the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
16
0

Year Published

2001
2001
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 31 publications
0
16
0
Order By: Relevance
“…We used a derivative of N ‐hydroxypyridine‐2(1 H )‐thione that generates hydroxyl radicals upon photolysis to induce cleavage of r(CUG) exp . Previous studies have used N ‐hydroxypyridine‐2(1 H )‐thione to probe RNA structure in vitro 12. Thus, we synthesized 1‐hydroxy‐6‐thioxo‐1,6‐dihydropyridine‐2‐carboxylic acid (N‐HPT) to conjugate a hydroxyl‐radical‐producing warhead onto 2H‐4 using an amide bond (2H‐4‐HPT; Figure 2).…”
Section: In Vitro Potencies Of 2h‐4 2h‐4‐hpt and N‐hpt For The Inhimentioning
confidence: 99%
“…We used a derivative of N ‐hydroxypyridine‐2(1 H )‐thione that generates hydroxyl radicals upon photolysis to induce cleavage of r(CUG) exp . Previous studies have used N ‐hydroxypyridine‐2(1 H )‐thione to probe RNA structure in vitro 12. Thus, we synthesized 1‐hydroxy‐6‐thioxo‐1,6‐dihydropyridine‐2‐carboxylic acid (N‐HPT) to conjugate a hydroxyl‐radical‐producing warhead onto 2H‐4 using an amide bond (2H‐4‐HPT; Figure 2).…”
Section: In Vitro Potencies Of 2h‐4 2h‐4‐hpt and N‐hpt For The Inhimentioning
confidence: 99%
“…Among the sequences noteworthy here were RTL3 , poly(A) RNA polymerease , and histone methyltransferase , which the first two encode RNA processing enzymes and third one catalyzes histone methylation. Histone methylation and alternative RNA polyadenylation have been shown to be strongly correlated with light regulation of the gene expression in plants [ 35 38 ]. However, it’s not clear if these enzymes themselves could also be regulated by DNA methylation.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, it has been shown that peroxynitrous acid is useful for analyzing events with half-lives of greater than ∼3 seconds. [19][20][21] The reagent is synthesized by oxidation of potassium peroxynitrite with peroxide followed by trapping with potassium hydroxide to yield the stable potassium salt. 22 Addition of potassium peroxynitrite to aqueous solutions buffered to pH 7 produces peroxynitrous acid which decomposes with a half-life of less than a second to generate hydroxyl radicals (Fig.…”
Section: Equilibrium and Kinetic Generation Of Hydroxyl Radicalsmentioning
confidence: 99%